Penggunaan dan Kepuasan terhadap Video Pendek melalui Media Sosial TikTok: Systematic Literature Review - Rusman, Almira Adani; Adistri, Nabila; Irwansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
In the ever-changing internet era, mobile media consumption has shifted significantly from text content to video content. Short video applications serve as a solution to fill fragmented free time, offering fast and easily accessible entertainment. These videos often have diverse content and can interact with each other across platforms, allowing users to engage more deeply and enjoy a more dynamic viewing experience. Since the advent of the Internet, uses and gratifications theory has also been applied to various types of digital platforms, for example, to help understand the role of E-WoM moderation and traditional media advertising in choosing fast food outlets. This study aims to analyze user motivations and satisfactions in using TikTok as a digital platform with uses and gratifications theory (UGT). This study uses the Systematic Literature Review method to obtain research data. The results of this study indicate that uses and gratifications theory (UGT) has a relationship with awareness and use of TikTok social media. There are several drives and motivations that each user has related to the use of TikTok social media, especially the FYP feature, namely entertainment, media for self-expression, escape from reality, and user loyalty to access certain content.